RIPK1 kinase drove brain microvascular endothelial cells death and blood-brain barrier disruption in neonatal Escherichia coli meningitis - Xuhang Wang; Yuhan Zhang; Xinru Chen; Kailai Fu; Jiaqi Cui; Jiaoling Wu; Yu Sun; Jianluan Ren; Feng Xue; Jianjun Dai; Fang Tang (Nature Communications)
Abstract Neonatal meningitis Escherichia coli (NMEC) breaching the blood-brain barrier (BBB) is a critical event in the development of E. coli meningitis. Brain microvascular endothelial cells (BMECs), the primary structural component of the BBB, play a central role in defending against pathogen invasion. In this study, we employ the NMEC strain RS218 (O18:K1:H7) to investigate the molecular mechanisms of cell death in BMECs and its pivotal contribution to BBB disruption. The study reveals that RS218 infection promotes assembly of the Ripoptosome complex. This leads to the coordinated activation of apoptosis, pyroptosis, and necroptosis. Notably, necroptosis can also occur through RIPK1-independent pathways. By generating Ripk1 D138N/D138N , Gsdmd -/- , and Casp8 -/- Ripk3 -/- mice, we demonstrate that the regulation of BMECs death was an important factor in BBB resistance to infection. Among these models, kinase-dead Ripk1 D138N/D138N mice exhibit the most effective BBB protection, independent of innate immune responses. Inhibition of RIPK1 kinase significantly preserves BBB integrity, and lowers RS218 invasion and neuroinflammation. Moreover, the combination of RIPK1 inhibition with antibiotics yields additive therapeutic effects. Our study advances the understanding of NMEC pathogenesis and supports the potential of RIPK1 as a therapeutic target for E. coli meningitis.